Synthesis, Characterization and Evaluation the Biological activity for New Mesogenic 1, 3-oxazepine-4, 7-dione Derived from Trimesic Acid - Nasreen R. Jber (Journal of Global Pharma Technology, 2016)
In this work new liquid crystalline oxazepine compounds derived from trimestic acid were prepared. In the first step, 1, 3, 5-tris-[3-thiol-4-amino-1, 2, 4 triazole-5-yl] benzene [E] was synthesized through the preparation of 1, 3, 5-benzenetricarboxylic acid hydrazide [C]. The second step was the condensation reaction between different aldehydes: 4-hexyloxybenzaldehyde, 4-heptyloxybenzaldehyde and 4-octyloxybenzldehyde to yield new Schiff bases compounds [F1-F3] respectively. In the final step, oxazepine compounds [G1-G3] were prepared from reaction imines compounds [F1-F3] with succinic anhydride in dry benzene. All these derivatives were characterized via FTIR spectroscopy, elemental analysis and 1H-NMR spectroscopy. Polarizing optical microscope and DSC were used to assessment the mesomorphic properties of the synthesized compounds. The synthesized compounds [G1-G3] were examined for antibacterial activity against Staphylococcus aureous, Staphylococcus saprophyticus (Gram-positive) and Kelebsiella pneumonia, Escherichia Coli (Gram-negative).Keywords: 1, 3-oxazepine-4, 7-dione, 3-mercapto-4-amino- 1, 2, 4- triazole, Liquid cystal, Antibacterial activity.